Investors’ Perception of Corporate Governance : A Systematic Literature Review - Singh, Amit Kumar; Kapur, Vrinda (Arthshastra Indian Journal of Economics & Research, 2025)
The primary aim of effective corporate governance is to shield shareholders and other stakeholders from managerial discretion. Given the separation of ownership and control, as well as the diverse interests among stakeholders, it is essential to implement governance mechanisms that harmonize stakeholders’ interests. The present research conducted a comprehensive systematic review of existing literature on how awareness of corporate governance influences investment choices. It emphasized the necessity of transparent and accountable governance practices to effectively meet investor expectations. Purpose : The purpose of this study was to examine the investors’ perception of corporate governance through a systematic literature review. Design/Methodology : The review was conducted by analyzing 17 published studies in the identified research area from Scopus and the Web of Science using PRISMA. The study examined how corporate governance mechanisms impacted the way investors perceive a company. Findings : Strong corporate governance fostered trust and confidence among investors. When companies demonstrated ethical behavior, fairness, and shareholder rights protection, investors were more likely to engage in long-term investment relationships. Investors were more willing to provide equity or debt instruments to companies they perceived to have reliable governance structures. Practical Implications : The systematic review highlighted several actionable recommendations for stakeholders aiming to improve how investors perceive corporate governance. Companies should prioritize transparent disclosure, bolster board independence, and link executive compensation to performance. Initiatives to educate investors about governance practices should be intensified, and policymakers might explore enhancing regulatory oversight and advocating best practices. Originality : To the best of our knowledge, no similar systematic review has been conducted on this topic. However, such reviews provided a clearer understanding of how topics evolved within extensive research traditions and helped identify primary findings and ongoing research directions.